2020
DOI: 10.17977/um039v5i22020p137
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Media Belajar Model-Model Boneka Dari Bahan Kain Flanel Berdasarkan Tema Kegiatan Untuk Pembelajaran Anak Usia Dini

Abstract: Pemanfaatan media pembelajaran yang tepat di TK dapat mengembangkan berbagai kemampuan anak dengan baik, tetapi sebaliknya apabila penggunaan media kurang menarik bagi anak, anak akan cepat bosan dan tidak tertarik lagi dengan pembelajaran yang diberikan oleh guru. Tujuan penelitian ini adalah untuk mengembangkan media pembelajaran model-model boneka yang dapat digunakan untuk mengembangkan kemampuan bahasa ekspresif anak dalam bercerita sesuai dengan jenis tema kegiatan yang ada di TK.. Penelitian ini merupak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
3
0
1
Order By: Relevance
“…According to research by Usep Kustiawan et al (2020), which aimed to develop learning in enhancing children's language skills in accordance with the theme of activities by using puppets, it indicated that hand puppets had high attractiveness and were easy to use (Usep Wuri Astuti;Munaisra Tri Tirtaningsih, 2020). This was supported by the Jatmikowati who stated that the learning materials of early childhood education were very effective when performed through role-playing centers, and it requires supportive learning media such as puppets (Jatmikowati et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…According to research by Usep Kustiawan et al (2020), which aimed to develop learning in enhancing children's language skills in accordance with the theme of activities by using puppets, it indicated that hand puppets had high attractiveness and were easy to use (Usep Wuri Astuti;Munaisra Tri Tirtaningsih, 2020). This was supported by the Jatmikowati who stated that the learning materials of early childhood education were very effective when performed through role-playing centers, and it requires supportive learning media such as puppets (Jatmikowati et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Akan tetapi pemanfaat media dan sumber belajar sederhana seperti sketsa gambar, kartu, buku dan lain-lain yang bersifat visual dan konvensional, tidak akan luput atau tertinggal zaman dan membuat kegiatan belajar menjadi menarik dan kooperatif. (Kustiawan, 2016). Inti dari pemanfaatan media pembelajaran bertujuan agar meingkatkan efesiensi dan efektivitas pengajaran (Nurmadiah, 2016).…”
Section: Abstrakunclassified
“…Learning media is a tool to convey stimuli in the form of material to stimulate thoughts, feelings, and visions that lead to the learning process [5]. According to Kustiawan, Astuti, & Tirtaningsih [6], learning media is a communication tool to convey information in material from the teacher to students during teaching and learning activities so that students are interested in receiving learning. So, it can be concluded that learning media, other than containing a material or teaching material, can attract students' attention and concretize something abstract.…”
Section: Introductionmentioning
confidence: 99%